Heutagogy: Empirical study on conceptual understanding, self-learning awareness and learning outcomes - Rinaldi Rinaldi; Deni Wahyuni; Isa Hamzah (Universitas Negeri Padang, 2022)
Some problems are attached by the online learning system such as low self-learning awareness and conceptual understanding. One of the learning approaches is the concept of heutagogy which is the development of andragogy approach. Self-learning awareness and conceptual understanding are needed either online or offline learning system, so it can improve student learning outcomes in all subjects. However, previous studies on the effect of the heutagogy approach on self-learning awareness and conceptual understanding as well as relate it to increase learning outcomes is still limited. Likewise with research on how the influence of self-learning awareness, conceptual understanding and their interaction on increasing learning outcomes has not been found. As novelty, this study aims to determine the effect of the heutagogy approach on increasing conceptual understanding and self-learning awareness and the interaction effect of self-learning awareness and conceptual understanding on course learning outcomes. This study is quasi-experiment. A total of 250 first-year students were randomly selected as samples in the pre-test and post-test. Data were collected by distributing a set of questionnaires and a set of exams via Google forms and were analyzed using Statistical Package for Social Science 23.0 (SPSS v 23.0) and SmartPLS 3.0. Findings showed that the heutagogy approach has possitive and significant effect to increase conceptual understanding and self-learning awareness. Self-learning awareness has a positive and significant effect and also mediates the effect of conceptual understanding on learning outcomes. Heutagogy approach increase conceptual understanding (8.79%), self-learning awareness (10.68%), and learning outcomes (6.70%) compared with traditional method.